Neurokinin receptor antagonists as potential non-hormonal treatments for vasomotor symptoms of menopause - Melissa Conklin; Nanette Santoro (SAGE Publishing, 2023)
Vasomotor symptoms of menopause (VMS), otherwise known as hot flashes, can significantly impact women's quality of life. Up to 87% of women report hot flashes during or after their menopause transition, and can last for a median duration of 7.4 years. The current mainstay of treatment and the most effective treatment for VMS is hormone therapy with estrogen. However, hormone therapy is not without risk, and the discovery of an effective nonhormonal treatment option with neurokinin B receptor antagonists for VMS provides an encouraging and potentially practice-changing treatment option for all women. This review will discuss the pathophysiology and mechanism of action, as well as review the current compounds in development targeting the neurokinin receptors.